Characteristics and reported injuries of recreational and competitive archers - Prine, B. R.; Pazik, M. N; Prine, A.; Haley, H.; Bruner, M. L.; Vincent, H. K. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: The aim of this cross-sectional study was to describe basic characteristics of archery athletes and examine injuries reported among archers of a variety of demographic and experience levels. METHODS: Participants at various archery competitions were asked to complete a 27-item survey that included demographics, bow type, archery experience, archery training patterns and volume, and injury incidence and anatomical location. RESULTS: Two hundred and thirty-four complete surveys were included in the analysis. No significant differences were noted between archery experience groups for age, height, weight, or draw length. A significant difference for draw weight was noted between beginners and advanced level (P=0.045) and between intermediate and advanced archers (P=0.013). Expert level archers reported participating in archery the most days per week (4.9±1.6) and months per year (11.6±0.9) out of all experience levels. Archers using recurve bow types reported more injuries (54 in total) than archers using compound bows (that were 47). The highest percentage of injuries due to archery was found at the expert/professional level with 50% of that group acquiring an injury. The shoulder was the most reported anatomical site of injury (with a total of 69 cases) followed by the back (30 cases) and elbow (19 in total). CONCLUSIONS: Injury rates in archery are comparable to other sports such as golf and tennis, thus establishing archery as a sport with legitimate risks to athletes. Also, there are several factors within the sport that predispose participants to injury. It is crucial that participants are informed of these risks and that appropriate training and equipment decisions are made to optimize the reduction of injury prevalence.